2022
DOI: 10.3390/min12020206
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Geochemistry and Genesis of Beryl from Wadi Nugrus, South Eastern Desert, Egypt

Abstract: Beryl occurs in the ancient Roman mines at Wadi Nugrus, South Eastern Desert of Egypt. It ranges from small crystals to 10 mm in size, and it varies in color, appearing as bright green, pale green, dark green and brown-green with biotite inclusions. The trace and minor elements were analyzed by the SIMS method. The two rims are richer in Cs, Na, Mg, Fe, Sc, V, Rb and H2O than cores but are poor in Mn, Ca, Co, Sr and Li. The bright-green rim is richer than the pale-green one in Na, P, K, Ca, Fe, Rb, Cs and F, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…The mean estimated outdoor annual effective dose (AED out ) values are 0.07 mSv y −1 for W. Ghazala, 0.06 mSv y −1 for W. Sedri, 0.16 mSv y −1 for Homret Mukpid, 0.05 mSv y −1 for Igla, 0.11 mSv y −1 for Zabara-Um Addebaa belt and 0.15 mSv y −1 for Homret Akarem, which are comparable with the recommended level of 45 (0.07 mSv y −1 ).…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…The mean estimated outdoor annual effective dose (AED out ) values are 0.07 mSv y −1 for W. Ghazala, 0.06 mSv y −1 for W. Sedri, 0.16 mSv y −1 for Homret Mukpid, 0.05 mSv y −1 for Igla, 0.11 mSv y −1 for Zabara-Um Addebaa belt and 0.15 mSv y −1 for Homret Akarem, which are comparable with the recommended level of 45 (0.07 mSv y −1 ).…”
Section: Resultssupporting
confidence: 56%
“…Abdalla 44 reported Be concentrations with a range of 0.001–0.007% in beryl-bearing granitoids (Homret Akarem, Homret Mukpid, and Qash Amir) in the Eastern Desert of Egypt. Abdel Gawad et al 45 investigated the geochemistry and genesis of beryl crystals (up to 10 mm in size) from the ancient Roman mines at Wadi Nugrus, SED, Egypt. They reported that the emerald of Wadi Nugrus occurs along the contact zone between biotite schists, pegmatites, and quartz veins, and has similarities with the geological setting of the Canadian emeralds 45 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations